Persistent wrist monarthritis: down to the bone. (27th February 2018) - Cheah, Jonathan Toh Leong; Fields, Theodore R
Abstract : A minority of osteoid osteomas are found to be juxta-articular and within the small bones of the wrist. We present a 30-year-old man diagnosed with an osteoid osteoma of the lunate bone, presenting with 3 years of left wrist pain, swelling and reduced range of motion. Given the patient's background and laboratory testing, consideration was given to both inflammatory and infectious causes and the diagnosis was delayed, requiring repeat interval imaging and assisted by multiple imaging modalities. Management by surgical excision led to resolution of pain and swelling. In cases of a prolonged isolated monarthritis, juxta-articular osteoid osteoma should be considered in the differential.